Trastornos motores esofágicos y su relación con el reflujo gastro-esofágico a través de manometría de alta resolución - Ríos Touma, Carla María (2017)
Context: with the advent of high resolution manometry, it has been easier to diagnose the different esophagueal motility disorders, that are determined by the Chicago Classification (11). The symptoms of the different disorders are diverse, finding the same symptom in different motor alterations, especially the ones related to gastroesophagueal reflux disease (GERD). Ineffective esophagueal motility (IEM) is one of the most frequent motor disorder, that has been directly related to GERD, reason why it is proposed that the motor disorder can change according the natural evolution of the disease (1,13).Objective: to determine the prevalence of the different esophagueal motor disorders in patients subjected to high resolution manometry in the digestive physiology laboratory of Hospital ‘’Carlos Andrade Marin” between May and November of 2015 and the relation between typical or atypical reflux symptoms.Methodology: we carry out a prevalence study, where 71 high resolution manometries were analyzed to determine the frequency of the different esophagueal motility disorders and its relation to typical or atypical reflux symptoms.Results: a total of 71 high resolution manometries were analyzed, 40 women (56.33%) and 31 men (43.66%), with a mean age of 52.28 years (19-91 years). Of the total of analyzed manometries, 30 (42.25%) demonstrated any esophageal motor disorder, being ineffective esophageal motility the most frequent finding, covering 56,66% of all motor disorders. In general, the principally symptoms of patients are GERD typical symptoms, mainly in IEM, because 82.35% of this patients presented the symptoms.Conclusions: ineffective esophageal motility is the most frequent motor disorder and is highly related to typical GERD symptoms. New studies are required with a larger sample of patients to determine the risk of patients with GERD to develop one or other esophagueal motor disorder and determine the prevalence of other esophageal motor disorders that were not found in the study.